ANAYSIS OF FACTORS AFFECTING PROFITABILITY IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - SUSI IDELLA SIAHAAN; Poniman (Jurnal Mantik, 2022)
A company is established one of which aims to achieve the maximum possible profit, to increase the prosperity of the owners or shareholders, one of which is through the company's ability to pay dividends. This study aims to determine the effect of CR, TATO, DER on Return on asset listed on the Indonesia Stock Exchange. The population in this study consisted of 12 pharmaceutical sector companies listed on the Indonesia Stock Exchange for the period 2017 - 2021. The sampling technique in this study used the purposive sampling method so as to obtain 8 companies that met the criteria, by processing data using the IBM SPSS 25 program. Method of analysis The data used in this research are descriptive statistical analysis, classical assumption test, multiple regression analysis, and hypothesis testing. The results of the t-test obtained are CR, TATO has a positive effect on Return on asset, while DER has a negative effect on Return on asset. And it is concluded that the coefficient of determination that occurs is 0.595 which indicates that 59.5% of the independent variables are quite effective on Return on asset, while the remaining 40,5%.